Ethnic Value in Toraja’s Social Ritual: Cultural Education Perspective - Putra, Ahmad Suthami; Hijjang, Pawennari; Tang, Mahmud (Newinera Publisher, 2023)
This article focuses on the examination of traditional burial rituals within the Toraja tribe. It compares the execution of funeral rites in the past, which were deemed customary, with those conducted in the late 1990s. By conducting a comparative analysis of the two ceremonies, it is anticipated that we may ascertain whether there has been any alteration in the execution of the ritual. According to Durkheim, the notion of the holy appears to be a genuine aspect of religious beliefs and practices in religious events. Religious individuals, when closely observed, distinguish between two distinct realms: the sacred realm and the profane realm. Sacred entities are consistently seen as superior, possessing great power, prohibited from engaging in regular interactions, and deserving of utmost reverence. Conversely, profane entities are mundane, unremarkable, and pertain to practical routines of everyday existence.